Fair scheduling with QoS support in wireless ad hoc networks. - Hsi-Lu Chao (IEEE Transactions on wireless communications)
We study fair scheduling with quality of service (QoS) support for wireless ad hoc networks. Two types of flows are considered: best effort and guaranteed flows. The goal is to satisfy the minimum bandwidth requirements of guaranteed flows and to provide a fair share of residual bandwidth to all flows. We compare timestamp-based and credit-based mechanisms, and evaluate the feasibility of all existing fair scheduling schemes of these two types of mechanisms for multimedia wireless multihop networks. We suggest a flow weight calculation scheme for existing timestamp-based mechanisms to support both best effort and guaranteed flows, and propose a credit-based mechanism called credit-based slot allocation protocol (CSAP) for fair scheduling with QoS support. For comparison purposes, several metrics are defined to evaluate the performances of these two kinds of mechanisms. The simulation results show that CSAP outperforms the other approaches in terms of meeting the minimum requirements of guaranteed flows, fairly sharing the residual bandwidth among all flows, and improving overall system throughput.